Faktor-faktor yang berhubungan dengan keluhan nyeri punggung bawah pada buruh di Balai Besar Kekarantinaan Kesehatan Makassar - Rombe, Aneke A Linda; Ayumar, Andi; Basri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Low back pain is the most common musculoskeletal complaint and the leading cause of disability worldwide, with a prevalence ranging from 20% to 33% among all patients with musculoskeletal pain. Low back pain is not only experienced by the elderly but can also occur across all age categories, including the productive adult age group. Factors that may contribute to low back pain include age, length of service, workload, and duration of work. The aim of this study is to determine the relationship between age, length of service, workload, and work duration with complaints of low back pain. Methods: This study is an observational analytic study with a cross-sectional approach. The population consists of all laborers at the Makassar Health Quarantine Center. The sample comprises 133 respondents from the population of laborers working at the Makassar Health Quarantine Center. The sampling technique used is random sampling with the Slovin formula. The measuring instrument used is the Numeric Rating Scale questionnaire. The statistical test employed is the Chi-Square Test, with Fisher's Exact Test as an alternative. Findings: The results of the study show a significant relationship between age (p-value ρ=0.000<0.05), length of service (ρ=0.000<0.05), workload (ρ=0.009<0.05), and work duration (ρ=0.000<0.05) with complaints of low back pain among laborers. Conclusion: The study concludes that there is a relationship between age, length of service, workload, and work duration with complaints of low back pain among laborers at the Makassar Health Quarantine Center. It is recommended that the Makassar Health Quarantine Center conduct regular medical check-ups for laborers, provide adequate work hours, and monitor and reduce the burden lifted by laborers.